Class and Indigenous Politics: the Paradox of Seediq/Taroko Women “Entrepreneurs” in Taiwan - Scott Simon (New Proposals, 2011)
Class is an important concept in studying the political economy of indigeneity. This paper looks at the role of women shopkeepers in Seediq and Taroko indigenous communities in Taiwan from a perspective of Marxian class analysis. By creating and controlling social and political space in their shops, they become key players in local political struggles that reinforce a bipolar class structure composed of a small elite class and a vast lumpenproletariat. In some cases, they may even be able to launch themselves or family members into positions of political power. This phenomenon is an integral part of the capitalist system that expropriates indigenous land, labour and natural resources. In fact, the creation of new elites in previously egalitarian societies makes such expropriation possible in the first place.